2023
DOI: 10.7759/cureus.36567
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Financial Conflicts of Interest and Quality of Evidence Underlying the American Diabetes Association Clinical Practice Guidelines: The Standards of Medical Care in Diabetes, 2021

Abstract: Background: Clinical practice guidelines make recommendations based on the best available evidence. Proper management and disclosure of financial conflicts of interest (FCOIs) are necessary for trustworthy clinical practice guidelines. This study evaluated the prevalence of FCOIs and quality of evidence underlying the American Diabetes Association (ADA) guidelines.Methods: Using the Open Payments Database (OPD) between 2018 and 2020, we examined the research and general payments to all authors of the Standards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…6 Although some CPGs developed in the 2010s did not meet these recommendations, many recent studies have shown improvements in COI management strategies in CPGs developed after the late 2010s. 2 , 4 , 82 , 83 , 84 , 85 , 86 Our study, however, has repeatedly demonstrated that nearly all Japanese CPG authors across specialties received significant payments for activities like delivering lectures and consulting services, leading to direct income. 3 , 5 , 18 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 87 , 88 , 89 , 90 , 91 Although the authors acknowledge the importance of collaboration between physicians and the health care industry in improving patient care, it is imperative to develop trustworthy and evidence‐based CPGs without establishing a group where >94% of the experts have substantial financial ties to the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…6 Although some CPGs developed in the 2010s did not meet these recommendations, many recent studies have shown improvements in COI management strategies in CPGs developed after the late 2010s. 2 , 4 , 82 , 83 , 84 , 85 , 86 Our study, however, has repeatedly demonstrated that nearly all Japanese CPG authors across specialties received significant payments for activities like delivering lectures and consulting services, leading to direct income. 3 , 5 , 18 , 22 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 87 , 88 , 89 , 90 , 91 Although the authors acknowledge the importance of collaboration between physicians and the health care industry in improving patient care, it is imperative to develop trustworthy and evidence‐based CPGs without establishing a group where >94% of the experts have substantial financial ties to the pharmaceutical industry.…”
Section: Discussionmentioning
confidence: 78%
“…Clinical practice guidelines (CPGs) provide recommendations for disease management and treatment, grounded in the best available scientific evidence. However, financial conflicts of interest (COIs) between the pharmaceutical industry and CPG developers could introduce bias in these recommendations, potentially favoring the industry, 1 , 2 , 3 , 4 , 5 and thus, potentially jeopardizing patient care. 5 , 6 , 7 Also, significant and widespread financial COIs could easily call into question the validity of CPG recommendations from the public and undermine readers' trust in the CPG recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike leading physicians conducting clinical trials and research sponsored by the industry, leading physicians, such as clinical practice guideline authors, society board members, and academic journal editors, are necessary to manage and, if possible, be free from financial interest with the industry, as their financial interest with industry conflict with their primary interest [6,7,[9][10][11]33,41,42,81,82,[85][86][87][88]. Currently, FCOIs among clinical practice guideline authors are strictly managed by many guideline-developing organizations: the minority of guideline authors with FCOIs involve in guideline development, all FCOIs for the past three years are declared and disclosed by guideline authors, and the guideline chairperson is required to be free from any FCOIs with industry [11,81,84,86,[88][89][90]. Several academic journals, such as the Annals of Emergency Medicine, the official journal of the American College of Emergency Physicians, and the Journal of Urology, the official journal of the American Urological Association, disclose the editors' FCOIs on journal webpages [75].…”
Section: Discussionmentioning
confidence: 99%
“…1 , 2 However, the integrity of these guidelines can be compromised by conflicts of interest (COIs). 3 , 4 , 5 Given that current increasing attention from pharmaceutical companies to diabetologists 6 , 7 and large prevalence of diabetes and obesity, proper management of financial COIs is essential for trustworthy diabetes CPGs. 1 Despite the critical nature of this issue, no research has investigated these financial relationships in the Japanese context.…”
mentioning
confidence: 99%